2023
DOI: 10.1007/s00234-023-03251-5
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning reconstruction for improving the visualization of acute brain infarct on computed tomography

Naomasa Okimoto,
Koichiro Yasaka,
Nana Fujita
et al.

Abstract: Purpose This study aimed to investigate the impact of deep learning reconstruction (DLR) on acute infarct depiction compared with hybrid iterative reconstruction (Hybrid IR). Methods This retrospective study included 29 (75.8 ± 13.2 years, 20 males) and 26 (64.4 ± 12.4 years, 18 males) patients with and without acute infarction, respectively. Unenhanced head CT images were reconstructed with DLR and Hybrid IR. In qualitative analyses, three readers evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…A higher interobserver agreement in the evaluation of ILD for DLR would have been resulted from an improved image quality. A better image noise reduction can be achieved compared to HIR in various regions such as the head, 19,27 vertebra, 21,23,24 and abdomen 20,22 as well as the chest. 25 Our study result corroborates with other studies, which revealed a significantly reduced quantitative image noise in DLR compared to HIR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher interobserver agreement in the evaluation of ILD for DLR would have been resulted from an improved image quality. A better image noise reduction can be achieved compared to HIR in various regions such as the head, 19,27 vertebra, 21,23,24 and abdomen 20,22 as well as the chest. 25 Our study result corroborates with other studies, which revealed a significantly reduced quantitative image noise in DLR compared to HIR.…”
Section: Discussionmentioning
confidence: 99%
“…It was trained with paired data, one with low noise and high spatial resolution and another with noise contamination and learned the difference between noise and signal. 17,18 It has been reported that the appropriate algorithm of DLR can improve image quality of CT images in various body regions 19-24 including the lung, 25 we hypothesized that this reconstruction algorithm could also potentially improve the interobserver agreement in the evaluation of honeycombing in patients with ILD.…”
Section: Introductionmentioning
confidence: 99%
“…In supervised training of DLR, low-quality data and high-quality images are respectively used as the input and reference data. A trained DLR is known to reduce image noise [ 19 ], thereby improving the quality of CT images in regions as varied as the head [ 20 , 21 ], chest [ 9 ], abdomen [ 10 , 19 , 22 , 23 ], and vertebrae [ 11 , 24 , 25 ]. We therefore hypothesized that DLR can also improve the quality of high-resolution CT of the temporal bone.…”
Section: Introductionmentioning
confidence: 99%